BUSINESS FEASIBILITY STUDY OF HEALTHY FOOD RESTAURANT IN BEKASI - Steffani Novenia Wimartanti; Sonny Sonny (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The increasing of health awareness and the concern of long-term effect from artificial seasoning, healthy food’s trend has continuously increased in demand, along with the trend of a healthy lifestyle in recent years. The change in healthy food perception from time to time also helps with the healthy food demand in Indonesia. There are around 52.2% of the population in West Java who has carried out a healthy lifestyle. This research has the main objective to analyze Foresty Cookery’s (healthy food restaurant) in Bekasi by using financial feasibility as main analysis and industry feasibility as secondary. The financial use feasibility of investment such as Net Present Value (NPV), Payback Period (PP), and ratio analysis that consists of Return of Asset (ROA), and Return of Investment (ROI). The financial analysis shows Net Present Value is Rp1,489,209,200 (NPV> 0), Payback Period less than 3 years, and the following result of Ratio Analysis for the first year of business, where ROA is 10%, and ROI is 33%. Then for industry feasibility using Porter’s Five Forces and SWOT analysis, that resulted in low competitive rivalry, yet high risk of substitution. From both analysis on finance and industry feasibility, the analysis results indicated that the business has a profitable prospect and financially feasible. Keywords: feasibility study, business plan, entrepreneurship, healthy food restaurant